2021
DOI: 10.1371/journal.pone.0238336
|View full text |Cite
|
Sign up to set email alerts
|

Learning can be detrimental for a parasitic wasp

Abstract: Animals have evolved the capacity to learn, and the conventional view is that learning allows individuals to improve foraging decisions. The parasitoid Telenomus podisi has been shown to parasitize eggs of the exotic stink bug Halyomorpha halys at the same rate as eggs of its coevolved host, Podisus maculiventris, but the parasitoid cannot complete its development in the exotic species. We hypothesized that T. podisi learns to exploit cues from this non-coevolved species, thereby increasing unsuccessful parasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Although the active volatile compounds were not identified in this study, we provided evidence that the parasitoid ability to exploit such stimulus is strictly linked to its main host. However, some of the stimuli from host species in different life stages can be exploited by parasitoids at short range (Fatouros et al, 2005;Conti and Colazza, 2012;Bertoldi et al, 2021). For instance, T. japonicus recognizes tracks of H. halys females in arena bioassays (Boyle et al, 2020;Malek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the active volatile compounds were not identified in this study, we provided evidence that the parasitoid ability to exploit such stimulus is strictly linked to its main host. However, some of the stimuli from host species in different life stages can be exploited by parasitoids at short range (Fatouros et al, 2005;Conti and Colazza, 2012;Bertoldi et al, 2021). For instance, T. japonicus recognizes tracks of H. halys females in arena bioassays (Boyle et al, 2020;Malek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation of adult-related chemical odours is quite common in egg parasitoids 11 , 78 , 79 , however in the present study we noticed a lack of T. mitsukurii response to females of H. halys . Although it is known that volatile and non-volatile cues from physogastric females may represent reliable information for some Scelionid wasps, kairomones from stink bug females elicit parasitoid responses mainly at short distance 47 , 80 . For instance, a previous investigation demonstrated that T. japonicus responds to H. halys females only in a “short-distance” olfactometer and not in a “long-distance” olfactometer (as the one we have used here) 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Host quality may determine the value of the reward in oviposition learning, as it appears to affect memory consolidation in Cotesia glomerata and the egg parasitoid Trichogramma evanescens (Kruidhof et al, 2012), but not in the species Nasonia vitripennis and Nasonia giraulti (Hoedjes et al, 2014). Similarly, oviposition in non-hosts may either result in decreased interest in the non-host or associated volatiles, as is the case in C. kariyai (Aikawa et al, 2020;Steven et al, 2019), or to increased searching intensity, as found in the egg parasitoid Telonomus podisi (Bertoldi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%